2017
DOI: 10.1007/s00246-017-1775-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Heart Rate Variability in Adolescents with Abdominal Obesity

Abstract: Physical activity is a protective factor for autonomic dysfunction. However, whether this occurs in adolescents with abdominal obesity is still unclear. Thus, the aim of this study was to analyze the association between physical activity and heart rate variability (HRV) in adolescents with and without abdominal obesity. This cross-sectional study included 1152 boys (age: 17 ± 1 years). HRV measures of time (root mean square of the squared differences between adjacent normal RR intervals-RMSSD and the percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
3
24
0
2
Order By: Relevance
“…Third, given the correlation between physical steps and HRV, increasing physical activity might optimise HRV metrics. Although other studies have evaluated the association between physical activity and HRV, they were typically limited to small selected populations, 27,28 to participants in a narrow age range, 29 or relied on selfreported physical activity level. Due to the size of our dataset and method of measurement, we are able to exa mine the correlation between physical activity (quantified by daily steps from accelerometry) and HRV with greater precision, across a broad age range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, given the correlation between physical steps and HRV, increasing physical activity might optimise HRV metrics. Although other studies have evaluated the association between physical activity and HRV, they were typically limited to small selected populations, 27,28 to participants in a narrow age range, 29 or relied on selfreported physical activity level. Due to the size of our dataset and method of measurement, we are able to exa mine the correlation between physical activity (quantified by daily steps from accelerometry) and HRV with greater precision, across a broad age range.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several authors have discussed the effect of physical activity on HRV, and studies have shown beneficial results. [27][28][29][30] According to a study by one group, 31 the correlation between the number of steps measured by Fitbit devices compared with steps…”
Section: Introductionmentioning
confidence: 99%
“…Third, since we observe a strong correlation between physical steps and HRV, increasing physical activity may optimize HRV metrics. While there have been other studies of exercise and HRV, they have been typically limited to small populations (31,32) or to participants in a narrow age range (33). Due to the size of our dataset, we have been able to examine the correlation between exercise and HRV in more detail, for both young and older participants.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (31)(32)(33)(34) have discussed the effect of physical activity on HRV and studies have shown beneficial results. We analyzed the HRV of all participants (measured from 6 am -7 am) grouped by the average number of steps taken per day (steps per day is averaged over a 90 day period preceding the HRV measurement).…”
Section: Scaling Relationsmentioning
confidence: 99%
“…In a previous study by our group, 4 we observed, in a sample of 1152 male adolescents (aged 14 to 19 years), that high BP levels are directly associated with greater sympathetic modulation and less cardiac parasympathetic modulation, irrespective of the level of physical activity and the nutritional status, which also affect cardiac autonomic modulation. [5][6][7] The study "Family History of Hypertension Impairs the Autonomic Balance, but not the Endothelial Function, in Young Soccer Players" 8 sought to compare autonomic modulation, endothelial function and maximum oxygen consumption (VO 2max ) in young (healthy) athletes, divided according to their parents' blood pressure (BP) history, aiming to investigate the influence of genetic inheritance on these parameters. For that purpose, a cross-sectional study was carried out, in which 46 soccer players (18 ± 2 years old) were divided according to their parents' BP levels: 1) normotensive father and mother; 2) hypertensive father only; 3) hypertensive mother only; and, 4) hypertensive father and mother.…”
mentioning
confidence: 99%